Effect of a high-calorie diet on pro- to anti-inflammatory macrophage ratio through fat accumulation in rat lung tissue - Lestari, Indah Puji; Chozin, Iin Noor; Sartono, Teguh Rahayu; Sasiarini, Laksmi; Yudhanto, Hendy Setyo (Medical Journal of Indonesia, 2023)
BACKGROUND A high-calorie diet increases the risk of obesity. Accumulation of fat causes inflammation, as seen by the increased ratio of pro- to anti-inflammatory macrophages in a high-calorie diet. The pro-inflammatory shift in macrophage polarization may result in hypoxia, fibrosis, emphysema, and asthma. This study aimed to determine the effect of a high-calorie diet on pro- to anti-inflammatory macrophage ratio through fat accumulation. METHODS This experimental study used in vivo test in 16 male Sprague-Dawley rats aged 10–12 weeks. The rats were divided into high-calorie and normal diet groups for 16 weeks. Obesity in rats was defined as having a body mass index (BMI) of >0.68 g/cm2. Examination of lung fat accumulation was done through oil red O staining, while pro- to anti-inflammatory macrophage ratio was tested through CD11c and CD206 expressions by immunohistochemical method. RESULTS The high-calorie diet group had higher BMI (0.72 [0.02] versus 0.62 [0.03]; p<0.001), lung fat accumulation (32.73 [10.55] versus 0.37 [0.38]; p<0.001), and pro- to anti-inflammatory macrophage ratio (0.83 [0.02] versus 0.24 [0.006]; p<0.001). The higher the fat accumulation, the higher the pro- to anti-inflammatory macrophage ratio (r = 0.933; p<0.001). CONCLUSIONS The ratio of pro- to anti-inflammatory was higher in the high-calorie diet group, indicating polarization of macrophages toward pro-inflammatory macrophages.